Rasch Model for Analysis of Scientific Attitude Instruments in the Context of Secondary School Science Education - Nur Rizki Silviani Suryadi; Laila Nurmegawati; Siti Eneng Sururiyatul Mu’aziyah; Anggie Siti Perdani (CV. Dharma Samakta Edukhatulistiwa, 2025)
This study aims to analyze the psychometric quality of a scientific attitude questionnaire instrument for secondary school students using the Rasch Model. The instrument, developed based on Harlen’s theory, includes four key dimensions: curiosity, respect for data, critical thinking, and open-mindedness/cooperation. A survey method was employed with 30 seventh-grade students in Bandung City as respondents. Data were collected through a four-point Likert scale questionnaire and analyzed using Winsteps 4.6.0 software. The Results revealed that 16 out of 23 items fit the model based on Outfit Mean Square, Z-Standard, and Point-Measure Correlation indicators. The instrument also demonstrated high overall validity and reliability, with an Outfit MNSQ of 1.00, ZSTD of -0.17, an item separation index of 2.91, and a reliability coefficient of 0.89, indicating good discrimination and stable measurement structure. In conclusion, the scientific attitude instrument exhibits strong psychometric properties and can serve as a valid tool for assessing student attitudes in science education. However, revisions are needed for seven misfitting items to enhance clarity and construct alignment. Further validation on broader populations is recommended to ensure generalizability.